The Effect of Flashcard Usage on English Vocabulary Comprehension of Second-Grade Students at SD Negeri 10 Sitiung - Martiya Nurni Khairita; Rendi Marlianda; Anindhea Berliana (The Future of Education Journal, 2025)
The problem of this research is the low ability of students to comprehend English vocabulary, which was identified through observation and interviews with the English subject teacher at the school. The purpose of this study is to determine whether there is an effect of using flashcard media on vocabulary comprehension in the second-grade English class. This research uses an experimental method with a pre-experimental design. The study was conducted at SD Negeri 10 Sitiung during the second semester of the 2025/2026 academic year. The sample consisted of 17 students. The results of the independent sample t-test showed a significance of (0.000 < 0.005). It can be concluded that the use of flashcards has an effect on English vocabulary comprehension. Based on the pretest and posttest results, the use of flashcard media had a positive impact on vocabulary comprehension. Flashcards can be used by educators as one of the supporting media in the teaching and learning process and can increase student enthusiasm in participating in lessons.